(untitled) (London Journal of Engineering Research, 2025)
The question of demining sea raids and ports, which is relevant for Europe in the period of active deployment of military confrontations on its territory, is considered. It is proposed to combine the search capabilities of unmanned aerial vehicles (UAV) with the ability of trawler boats to clear floating mines. The optimal trajectory of search movements of UAV along the Archimedean spiral is proposed. An appropriate number of UAV that can effectively search for floating mines simultaneously is determined. Mine detonation with warheads dropped from an aerial liquidator drone is proposed as one of the most effective ways of the disposal of mines. The proposed method can be used to manage the search movements of UAV, to process the data provided by them about the detected floating mine, and to clarify the coordinates of the floating mine. A corresponding block diagram for computer software is proposed. It has been established that using the proposed search method and at the speed of UAV 5-5.5 m/s, it is possible to survey up to 6 square kilometers of sea every hour. At the same time, it is possible to save up to 20 liters of fuel for the trawler boat.